Whole-genome analysis of vancomycin-resistant Enterococcus faecium causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavaria, Germany - Eisenberger, David; Tuschak, Christian; Werner, Markus; Bogdan, Christian; Bollinger, Thomas; Hossain, Hamid; Friedrich, Petra; Hussein, Ziyad; Pöhlmann, Christoph; Würstl, Benjamin; Nickel, Silke; Lehner-Reindl, Verena; et al. (Journal of Antimicrobial Chemotherapy, 2020)
OBJECTIVES: Infections caused by vancomycin-resistant Enterococcus faecium (VREfm) represent a major public health concern due to limited treatment options. Among invasive isolates of VREfm, ST117, ST80 and ST78 represent the most frequently detected STs by MLST in Germany. In this study, we investigated the genetic diversity of isolates of VREfm recovered from different nosocomial outbreaks in Bavaria, Germany, by WGS. METHODS: Between January 2018 and April 2019, 99 non-replicate isolates of VREfm originating from nosocomial outbreaks at eight different hospitals in Bavaria were investigated for genetic diversity by WGS. In detail, complex types (CTs) were identified by core-genome MLST. Furthermore, an SNP analysis was performed for all VREfm strains. RESULTS: Most of the isolates of this study (76%) belonged to three major clonal groups, which occurred in at least three hospitals: ST80/CT1065 vanB (n = 45; six hospitals), ST117/CT71 vanB (n = 11; four hospitals) and ST78/CT894like vanA (n = 19; three hospitals). Moreover, isolates of the predominant lineage ST80/CT1065 vanB showed a maximum difference of 36 SNPs as revealed by SNP analysis. CONCLUSIONS: Whole-genome analysis of VREfm causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavarian hospital settings, namely ST80/CT1065 vanB, ST117/CT71 vanB and ST78/CT894like vanA. Further studies are needed for a better understanding of the factors affecting the successful spread of the above-mentioned lineages.
CRIS-Team Scopus Importer:2020-06-02